2015
DOI: 10.5897/ajar2013.7945
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of some ornamental plants to the socio-economic development of urban household in Akure metropolis

Abstract: This study examined the ornamental plant nursery business in Nigeria, using Akure Metropolis, Ondo State as a case study. The study specifically identified the factors affecting ornamental plant nursery operations and income generated and challenges of ornamental plant nursery business in the state. For the study ornamental nursery operators/owners households were surveyed across the study area and interviewed via the use of the questionnaire. Descriptive and the regression analysis were the tools used in anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
3
7
0
Order By: Relevance
“…The high involvement of male in tree nursery enterprise suggests that the business is not popular among the women in the study area. Larinde and Santus (2014) made similar observation in their study, male (78.9%) and female (21.1%), Adeduntan (2015) observed male (86%) and female (14%), Fakayodeet al (2008) recorded male (85.2%) and female (14.8% ), Abegundeet al (2009) recorded male (93.7%) and female (6.3%) while Khaguli (2007) observed men (87%) and (13%). This may be due to the fact that most of the operations performed in the nurseries are tedious and assumed to be men's work.The dominant age range among nursery entrepreneurs in the study area was between 30 and 39 years representing 36.7%.…”
Section: Resultssupporting
confidence: 74%
“…The high involvement of male in tree nursery enterprise suggests that the business is not popular among the women in the study area. Larinde and Santus (2014) made similar observation in their study, male (78.9%) and female (21.1%), Adeduntan (2015) observed male (86%) and female (14%), Fakayodeet al (2008) recorded male (85.2%) and female (14.8% ), Abegundeet al (2009) recorded male (93.7%) and female (6.3%) while Khaguli (2007) observed men (87%) and (13%). This may be due to the fact that most of the operations performed in the nurseries are tedious and assumed to be men's work.The dominant age range among nursery entrepreneurs in the study area was between 30 and 39 years representing 36.7%.…”
Section: Resultssupporting
confidence: 74%
“…However frankly, ornamental plants are having more roles to play especially the green of urban environment. In other country like Nigeria also, access to land for ornamental activities is in adequate (Adeduntan, 2015), implying that there is no effort taken by the city authority to designate and allocate land for ornamental nurseries. When the ornamental dealers at Mbezi site were interrupted due to expansion of Ubungo-Kibamba road, they attempted to seek land elsewhere in the city.…”
Section: A) Access To Land For Commercial Ornamental Nurseriesmentioning
confidence: 99%
“…In Africa, several challenges have been noted. In Nigeria, the study by Adeduntan (2015) show that there is inadequate access to land by ornamental nursery dealers growers. In Kenya, the development activities such as the expansion of roads interfere with the existing nurseries along the major road reserves (Otiso, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Akure Nigeria, it was revealed that the study carried on the contribution of some ornamental plants to the socio-economic development of urban households recorded that 38% for inadequate land, 52% for pest attack and 10% for water problems respectively. Major challenges of the florists in the city and other minor ones included the age of the operators and the lack of organized cooperative groups (Adeduntan, 2015). In US ecological studies have revealed that more than 50% of all invasive non-woody plant species and 85% of invasive woody plant species were originally introduced by plants used as ornamentals and other landscape purposes causing £35 billion annual loss in her economy (Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%